2021
DOI: 10.3390/antibiotics10060706
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility, Virulome, and Clinical Outcomes in European Infants with Bloodstream Infections Caused by Enterobacterales

Abstract: Mortality in neonates with Gram-negative bloodstream infections has remained unacceptably high. Very few data are available on the impact of resistance profiles, virulence factors, appropriateness of empirical treatment and clinical characteristics on patients’ mortality. A survival analysis to investigate 28-day mortality probability and predictors was performed including (I) infants <90 days (II) with an available Enterobacterales blood isolate with (III) clinical, treatment and 28-day outcome data. Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Bloodstream infections (BSIs) are an important cause of morbidity and mortality across all ages [ 1 4 ]. BSI is a relatively common complication of serious infections [ 5 – 7 ], and outcomes in patients with gram-negative bacteraemia are often poor [ 8 ], particularly when initiation of appropriate antimicrobial therapy is delayed [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bloodstream infections (BSIs) are an important cause of morbidity and mortality across all ages [ 1 4 ]. BSI is a relatively common complication of serious infections [ 5 – 7 ], and outcomes in patients with gram-negative bacteraemia are often poor [ 8 ], particularly when initiation of appropriate antimicrobial therapy is delayed [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four studies reported the association between bacterial VFs and neonatal mortality. One focused the analysis on sepsis due to E. coli [ 11 ], one on Klebsiella pneumoniae [ 5 ], the third analysed both E. coli and K. pneumoniae strains [ 12 ], and the last included a wider group of GNB ( E. coli , Klebsiella spp., Enterobacter spp., Serratia spp./ Proteus mirabilis ) [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used a genome-wide approach to investigate the impacts of a pathogen’s determinants on neonatal sepsis morbidity and mortality [ 5 , 12 , 13 ]. Studies investigating the association between number of virulence genes (VGs) and neonatal mortality showed opposite results.…”
Section: Resultsmentioning
confidence: 99%
“…Higher resistance rates of these bacteria could be considered as great threats and alarm the stakeholders to have more surveillance and control of the use of antimicrobials to combat infection. 10 12 …”
Section: Discussionmentioning
confidence: 99%
“…Laboratory sample : only human infection sample carried out by the Kirby–Bauer disk diffusion method as per Clinical Laboratory Standards Institute (CLSI) guidelines on Mueller–Hinton agar (Oxoid, Basingstoke, Hampshire, England). 7 , 11 …”
Section: Methodsmentioning
confidence: 99%